The Vietnamese Refugee Crisis of the 1970s and 1980s: A Retrospective View from NGO Resettlement Workers - Vu, Anna N.; Satzewich, Vic (Refuge: Canada's Journal on Refugees, 2016)
This article examines the role of NGO resettlement workers in refugee camps in Southeast Asia during the late 1970s and 1980s. The workers offered psychological support to refugees whose lives were in turmoil, but they also helped them present themselves in ways that would be most attractive to Western host countries. This process involves both commission and omission. NGO resettlement workers sometimes actively guided refugees by giving them specific advice and training. At other times, they facilitated this endeavour by observing how refugees fit themselves into the selection categories of various states, but chose to remain silent in order to avoid jeopardizing the refugees’ chances for resettlement.